ANALISIS TINGKAT KESEHATAN BANK DENGAN MENGGUNAKAN METODE RISK PROFILE, GOOD CORPORATE GOVERNANCE, EARNING, CAPITAL (RGEC) - Auliya Rokhmatika; Chairil Afandy (Management Insight: Jurnal Ilmiah Manajemen, 2017)
This research is conducted to detect the health level of Bank listed in indonesian stock exchange using RGEC period 2014-2015. RGEC is the aspect that most influence on the financial condition of banks, which also affect the health of banks. By using the NPL, LDR, IRR, NPM, ROA, NIM and CAR. Population in this study are all companies of Bank listed on stock exchange totaling 42 companies. Based on sampling criteria finally obtained sample is 21 companies of bank publish financial reports continuously in the period 2014-2015. The results obtained that the NPL from overall of bank sampel in 2014-2015 categorized is healthy. The results obtained that the LDR from sampel there’s counted 6 healthy categorized company enough. Companies categorized as unhealthy counted 6 bank. The results obtained from IRR variable there’s counted 2 healthy expressed bank and there’s counted 9 bank categorized as unhealthy. NPM variable obtained get result counted 8 bank categorized as unhealthy, there’s counted 7 bank categorized very healthy and 2 bank categorized healthy. ROA variable there’s counted 2 bank categorized as unhealthy and 3 bank categorized very healthy. NIM variable there’s counted 4 bank categorized healthy and 17 bank categorized as very healthy. CAR variable there’s counted 1 company categorized healthy and 20 company categorized very healthy.